Effects of lunar phases on short-term, explosive physical performance among young trained athletes - Yousfi, N.; Arbi Mejri, M.; Rouissi, M.; Hammami, A.; Tabben, M.; Chaouachi, A.; Haddad, M.; Chamari, K. (Chronobiology International, 2018)
Beliefs that lunar phases affect human physiology started in ancient times. Research has recently revealed that a physical fitness index increased in sedentary students at the new moon (NM) and full moon (FM) compared to other moon phases. However, the effect of lunar cycle (moon illumination and gravitational pull) on physical performance in athletes was not examined. Therefore, this study aimed to evaluate whether short-term explosive performance can be influenced by the different phases of the lunar cycle. Fourteen young male Taekwondo athletes (age: 16.9 ± 0.7 years, height: 159.7 ± 50.6 cm, body mass: 62.85 ± 7.84 kg) performed the following tests to assess the explosive physical performance during the different phases of the lunar cycle (NM, FQ (first quarter), FM, and LQ (last quarter)): maximal isometric manual contraction (dominant hand (MIMCD) and non-dominant hand (MIMCND)), maximal back isometric contraction (MBIC), squat jump (SJ), countermovement jump (CMJ), and 10-m sprint (10 m). The testing sessions during the different moon phases were performed in a counterbalanced order. The order of tests remained the same (MIMCD, MIMCND, MBIC, SJ, CMJ, and 10 m), and all sessions were performed in the evening (6:00 to 8:00 p.m.) on the first day of each evaluated lunar phase. Each parameter was measured over two consecutive lunar months in the calendar. Analysis of variance tests showed that there was no significant effect of lunar cycle on all explosive test measures, p > 0.05. Our results failed to identify any effect of lunar phase on evening explosive performance (mainly involving phosphagen pathway-based efforts) among young trained athletes. Therefore, it appears that moon phase/illumination does not affect short-term physical performance in young trained adolescents.